1995
DOI: 10.1111/j.1469-8749.1995.tb11944.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral and Psychosocial Functioning of Children With Opsoclonus‐myoclonus Syndrome

Abstract: SUMMARY Childhood opsoclonus‐myoclonus syndrome (OMS) is a movement disorder which typically strikes children in the early preschool years, seriously affecting intellectual, social‐emotional and general adaptive development. This series of 13 cases with well‐documented neurological histories, aged 1.7 to 16.3 years, provides an initial systematic evaluation of these children's neuropsychological, psychosocial and adaptive status. As expected, children with OMS had significantly reduced intelligence and severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 22 publications
3
14
2
Order By: Relevance
“…In terms of ataxia, our patients demonstrated a better outcome as compared with the cases in the literature [6,8,[12][13][14][15][16]. As shown in Table 1, only one of our patients had mild ataxia at follow-up; four were graded as minimal with normal gait and no motor handicap in everyday life, but they were not age appropriate in standing on one leg.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…In terms of ataxia, our patients demonstrated a better outcome as compared with the cases in the literature [6,8,[12][13][14][15][16]. As shown in Table 1, only one of our patients had mild ataxia at follow-up; four were graded as minimal with normal gait and no motor handicap in everyday life, but they were not age appropriate in standing on one leg.…”
Section: Discussioncontrasting
confidence: 45%
“…Papero et al [14] reported T scores of more than 60 in 7/8 of the children in the CBCL; IQ ranged from 50-87 and verbal fluency was disrupted in 12/13. In the study by Pohl et al [16], 32/54 patients had a learning disability and 33/54 a speech abnormality.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The prognosis of OMA associated with neoplasm has generally been poor. In children, the development of opsoclonus–myoclonus symptoms is often associated with permanent behavioral and cognitive deficits 13, 14…”
mentioning
confidence: 99%